The efficacy and safety of complementary and alternative medicine in the treatment of nausea and vomiting during pregnancy: A systematic review and meta-analysis - Tan, Mo-Yao; Shu, Shi-Hong; Liu, Run-Lei; Zhao, Qian (Frontiers in Public Health, 2023)
Background Complementary and alternative medicine (CAM) therapies are widely used for nausea and vomiting during pregnancy (NVP) due to the limitations of conventional medicine. However, their efficacy and safety remain controversial. Therefore, this meta-analysis was performed to assess the improvement of CAM therapy on NVP. Methods Randomized controlled trials (RCTs) were searched for where the trial group was CAM and the control group was a conventional medicine or a placebo for NVP. This was done via 8 databases, including PubMed, EMBASE, the Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, SinoMed, and VIP, from inception to October 25, 2022. The Grades of Recommendation, Assessment, Development and Evaluation (GRADE) was used to assess the quality of evidence. The Stata 15.0 software was used to perform the meta-analysis. Results Thirty-three RCTs were included in this study. The acupuncture treatment was superior to conventional medicine at the effective rate [RR = 1.71, 95% CI (1.02, 2.86), P = 0.042; Low-quality evidence]. Ginger had more significant effects than conventional medicine at the Rhodes index [WMD = −0.52, 95% CI (−0.79, −0.24), P ≤ 0.001; Moderate-quality evidence] and it had the same effect as drugs to relieve vomiting [SMD = 0.30, 95% CI (−0.12, 0.73), P = 0.160; Low-quality evidence]. Compared with placebo, ginger had a higher effective rate [RR = 1.68, 95% CI (1.09, 2.57), P = 0.018; Low-quality evidence], and lower Visual analog scale (VAS) of Nausea [WMD = −1.21, 95% CI (−2.34, −0.08), P = 0.036; Low-quality evidence]. Ginger had the same antiemetic effect as placebo [WMD = 0.05, 95% CI (−0.23, 0.32), P = 0.743; Low-quality evidence]. Acupressure was superior to conventional medicine at the reduction of antiemetic drugs [SMD = −0.44, 95% CI (−0.77, −0.11), P = 0.008; Low-quality evidence], and at the effective rate [RR = 1.55, 95% CI (1.30, 1.86), P ≤ 0.001; Low-quality evidence]. Acupressure had the same effect as placebo at the effective rate [RR = 1.25, 95% CI (0.94, 1.65), P = 0.124; Low-quality evidence]. Overall, CAM therapy was safer than conventional medicine or a placebo. Conclusion The results showed that CAM therapies were able to alleviate NVP. However, due to the low quality of existing RCTs, more RCTs with large sample sizes are needed to validate this conclusion in the future.